The 5-HT1B serotonin receptor regulates methylphenidate-induced gene expression in the striatum: Differential effects on immediate-early genes. (August 2017) - Alter, David; Beverley, Joel A; Patel, Ronak; Bolaños-Guzmán, Carlos A; Steiner, Heinz
Drug combinations that include a psychostimulant such as methylphenidate (Ritalin) and a selective serotonin reuptake inhibitor such as fluoxetine are indicated in several medical conditions. Co-exposure to these drugs also occurs with "cognitive enhancer" use by individuals treated with selective serotonin reuptake inhibitors. Methylphenidate, a dopamine reuptake inhibitor, by itself produces some addiction-related gene regulation in the striatum. We have demonstrated that co-administration of selective serotonin reuptake inhibitors potentiates these methylphenidate-induced molecular effects, thus producing a more "cocaine-like" profile. There is evidence that the 5-HT1B serotonin receptor subtype mediates some of the cocaine-induced gene regulation. We thus investigated whether the 5-HT1B receptor also modifies methylphenidate-induced gene regulation, by assessing effects of a selective 5-HT1B receptor agonist (CP94253) on immediate-early gene markers ( Zif268, c- Fos, Homer1a ) in adolescent male rats. Gene expression was measured by in situ hybridization histochemistry. Our results show that CP94253 (3, 10 mg/kg) produced a dose-dependent potentiation of methylphenidate (5 mg/kg)-induced expression of Zif268 and c- Fos . This potentiation was widespread in the striatum and was maximal in lateral (sensorimotor) sectors, thus mimicking the effects seen after cocaine alone, or co-administration of fluoxetine. However, in contrast to fluoxetine, this 5-HT1B agonist did not influence methylphenidate-induced expression of Homer1a . CP94253 also potentiated methylphenidate-induced locomotor activity. These findings indicate that stimulation of the 5-HT1B receptor can enhance methylphenidate (dopamine)-induced gene regulation. This receptor may thus participate in the potentiation induced by fluoxetine (serotonin) and may serve as a pharmacological target to attenuate methylphenidate + selective serotonin reuptake inhibitor-induced "cocaine-like" effects.